2019
DOI: 10.1186/s12951-019-0457-3
|View full text |Cite
|
Sign up to set email alerts
|

Specific drug delivery efficiently induced human breast tumor regression using a lipoplex by non-covalent association with anti-tumor antibodies

Abstract: BackgroundA cationic liposome-PEG-PEI complex (LPPC) was employed as a carrier for achieving targeted delivery of drug to human epidermal growth factor receptor-2 (HER2/neu)-expressing breast cancer cells. LPPC can be easily loaded with an anti-tumor drug and non-covalently associated with an anti-tumor antibody such as Herceptin that is clinically used to rapidly form immunoparticles within 1 h.ResultsDrug-loaded LPPC have an average size about 250 nm and a zeta potential of about 40 mV. Herceptin was complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…20,22,23 The properties of LPPCs allow them to strongly capture antigens or immunomodulators on their surfaces and be used as an adjuvant to trigger Th2 immune responses and antibody class switch. 24 LPPCs also strongly captured antibodies for specific drug delivery 25 and captures proteins for intracellular protein therapy. 26 In our previous study, LPPC was shown to protect BP structure against protein adsorption in the blood to preserve the drug's stability and cytotoxicity during transportation.…”
Section: Introductionmentioning
confidence: 99%
“…20,22,23 The properties of LPPCs allow them to strongly capture antigens or immunomodulators on their surfaces and be used as an adjuvant to trigger Th2 immune responses and antibody class switch. 24 LPPCs also strongly captured antibodies for specific drug delivery 25 and captures proteins for intracellular protein therapy. 26 In our previous study, LPPC was shown to protect BP structure against protein adsorption in the blood to preserve the drug's stability and cytotoxicity during transportation.…”
Section: Introductionmentioning
confidence: 99%
“…TZB modified NPs were effectively internalized and distributed near the nucleus within HER2-positive cancer cells 16 . Furthermore, in vivo studies revealed that TZB decorated liposome-PEG-PEI complex (LPPC) improved the site specific delivery of docetaxel-loaded LPPC to the tumor area but not to the healthy organs 17 . In addition, designing the NPs in the size range of 100-200 nm while applying a camouflaged surface coating, passive accumulation of these nanocarriers, resulting from their long circulation and enhanced permeation and retention, will synergize their active targeting 18 .…”
mentioning
confidence: 99%
“…5b, c). In combination with targeting molecules, LPPC has been shown to be a specific delivery vector for an antitumour drugs to tumour cells [36]. The targeting molecule RBDV-IgG1 Fc (RBDV) further causes specific gene transfection in vitro ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that LPPC can be complexed with proteins in a non-covalent linkage manner, and the bound proteins which still retain their biological activity cannot be displaced by unbound proteins [34,35]. With this property, LPPC has been used as a vector for targeted tumour therapy in combination with Herceptin [36]. However, the use of LPPC for targeting gene therapy has been still unknown.…”
mentioning
confidence: 99%